Sahidic Coptic Leviticus : Its Manuscript Witnesses and Its Text - Demiana, Antonia St, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
Until recently, the Sahidic Old Testament has received little attention. In Sahidic Coptic Leviticus , Antonia St Demiana fully documents, for the first time, the manuscript evidence of Sahidic Coptic Leviticus and offers a full codicological investigation and reconstruction of its codices and fragments. By surveying the dispersed Sahidic Leviticus fragments and folios, codices formerly considered to be independent of one another are reconstructed and unified, and new Leviticus fragments are identified and virtually assigned to their original codices. A semi-diplomatic edition of the most complete witness of Sahidic Leviticus, MLM M566, with the variae lectiones from the other Sahidic Leviticus witnesses is provided with a critical apparatus and English translation. A commentary including an introductory textual study and translation analysis of the text is also presented. In addition, this volume offers new and conclusive observations on the nature of the Sahidic version of Leviticus, and the relationship between the text of Sahidic Leviticus and its Greek Vorlage .